International Conference on Innovative Computing and Communications Proceedings of ICICC 2018, Volume 2 - Bhattacharyya, Siddhartha; Hassanien, Aboul Ella.; Gupta, Deepak; Khanna, Ashish; Pan, Indrajit; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book includes high-quality research papers presented at the International Conference on Innovative Computing and Communication (ICICC 2018), which was held at the Guru Nanak Institute of Management (GNIM), Delhi, India on 5-6 May 2018. Introducing the innovative works of scientists, professors, research scholars, students and industrial experts in the field of computing and communication, the book promotes the transformation of fundamental research into institutional and industrialized research and the conversion of applied exploration into real-time applications.
An Optimization Technique for Unsupervised Automatic Extractive Bug Report Summarization -- Prediction of Air Quality Using Time Series Data Mining -- Stress Analysis Using Speech Signal -- Leaf identification using HOG, KNN and Neural Networks -- Information Retrieval on Green Mining Dataset using Divergence from Randomness Models -- Arrhenius Artificial Bee Colony Algorithm -- Big Data in Health Care -- Halftoning Algorithm Using Pull Based Error Diffusion Technique -- Towards an Evolved Information Food Chain of World Wide Web and Taxonomy of Semantic Web Mining -- Topic Oriented Multi Document Summarization Using LSA, Syntactic and Semantic Features -- A Novel Framework for Automated Energy Meter Reading and Theft Detection -- Comparative Analysis of Privacy Preserving Data Mining Techniques.
Keywords: Computational intelligence; Telecommunication; Data mining; Computational Intelligence; Communications Engineering, Networks; Data Mining and Knowledge Discovery